(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the therapeutic potential of color psychology within the context of visual arts education. Special attention is given to the psychological and emotional effects of color on learners and the role of art based color activities in supporting emotional well-being and mental balance. The study analyzes how the conscious and pedagogically grounded use of color in visual arts classes can reduce emotional tension, enhance self-expression, and foster psychological resilience among students. Furthermore, the paper explores methodological approaches to integrating color therapy into art education and evaluates its effectiveness as a supportive pedagogical and psychotherapeutic tool. The findings suggest that color-based artistic activities not only contribute to students’ creative development but also serve as an important mechanism for emotional regulation and psychological support within the educational process.